2004
DOI: 10.1080/08830180490265556
|View full text |Cite
|
Sign up to set email alerts
|

Functions and Mechanisms of Action of the Adenovirus E3 Proteins

Abstract: In the evolutionary battle between viruses and their hosts, viruses have armed themselves with weapons to defeat the host's attacks on infected cells. Various proteins encoded in the adenovirus (Ad) E3 transcription unit protect cells from killing mediated by cytotoxic T cells and death-inducing cytokines such as tumor necrosis factor (TNF), Fas ligand, and TNF-related apoptosis-inducing ligand (TRAIL). The viral protein E3-gp19 K blocks MHC class-I-restricted antigen presentation, which diminishes killing by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 167 publications
2
136
0
7
Order By: Relevance
“…75,76 Viruses can modulate this balance. In the adenovirus system, for example, it has been shown that the existence of several virus-encoded proteins that block TNF-induced apoptosis [77][78][79] may be necessitated by the actions of the adenovirus E1A protein, which sensitizes cells to TNF, likely as a 'side effect' of its other biological activities. 58,80,81 In the experiments reported here, we were unable to observe significant cell death in response to TNF in the absence of cycloheximide in any of the cells tested (control cells, cells expressing high levels of E6 and cells expressing low levels of E6) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…75,76 Viruses can modulate this balance. In the adenovirus system, for example, it has been shown that the existence of several virus-encoded proteins that block TNF-induced apoptosis [77][78][79] may be necessitated by the actions of the adenovirus E1A protein, which sensitizes cells to TNF, likely as a 'side effect' of its other biological activities. 58,80,81 In the experiments reported here, we were unable to observe significant cell death in response to TNF in the absence of cycloheximide in any of the cells tested (control cells, cells expressing high levels of E6 and cells expressing low levels of E6) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The E3 region in these vectors is identical to the E3 region in KD3 allowing for overexpression of ADP in the absence of immunomodulatory E3 genes. 32 The TetON-EGFP and TetON-SEAP vectors were constructed for visualization 33 and quantification 30 of transgene expression, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Ad 'stealth' genes by RD Ad might also decrease immune-mediated clearance of the coinfected cell carriers in the immunocompetent host and lead to further improvement of antitumor efficacy. 32,51,52 Ad genome modifications introduced with the goal of improving the toxicity profile can compromise the oncolytic potency of the vectors due to attenuation of their replication in cancer cells as compared with wildtype (wt) Ad5. However, wt Ad5 can cause lethal outcomes in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…E3 proteins prevent Ad-infected cells from being cleared by cytotoxoic T lymphocyte, tumor necrosis factor, Fas ligand and tumor necrosis factorrelated apoptosis-inducing ligand and act to decrease systemic viral clearance. 59 Other adenoviral therapeutics have dysfunctional or deleted E3 regions for safety considerations. However, removal of the E3 region and rapid clearance of viral therapeutics may also cripple the antitumor effect.…”
Section: Telomelysinmentioning
confidence: 99%